The Appointment of Non-Muslim Leaders (Study of Surah Al-Mâ'idah verses 51 and 57 Using Semantic Approach) - Umum Budi Karyanto (ALSINATUNA, 2017)
It is a common thing that there is a controversy over non-muslim leadership in the majority of muslims. Historically,  this issue has been long-standing and has always been debatable among experts from time to time. As the result of this issue,Ulamas are divided into two groups, one of them is forbid the non-muslim issue, but others permit. Indonesia, which has muslim as the most population often experience a collision related to the appointment of non-muslim leaders. Essentially, leadership is a mandate that must be mandated to those who can afford it. Indonesian law guarantees all its citizens to emerge as both muslim and non-muslim leaders. Therefore, this paper attempts to analyze the appointment of non-Muslim leaders with a semantic approach according to verses of the Qur'ân that textually prohibit muslims (believers) to appoint non-muslims as leaders. It is because of the words waliy and auliyā'which textually have the meaning as "protector and leader". This paper used semantic approach refers to the basic and relational meaning to make it fairer in interpreting the text.